The Effect Local Ownership, Audit Quality, Audit Committee, And Financial Performance on Company Value - Fita Dwi lestari; Erna Setiany (Journal of Accounting and Finance Management, 2023)
Corporate value is used by management in running the business to maximize shareholder wealth. Local ownership, audit quality, audit committee, and financial performance have prospects in the future so that investors will be interested in investing. This population is in manufacturing companies that pay dividends during the period 2016 to 2021 which are listed on IDX so the sample used is 222 companies. The method used is panel data regression. Findings of local ownership, size audit, audit tenure, audit committee, total asset turnover, and return on assets have a significance on company value, on the contrary debt to assets has no significance on company value. It is suggested that companies can improve local ownership and audit quality in making corporate strategy decisions to increase company value, in addition to financial performance to maximize profits that reflect the company internally